Fuzzy fault tree analysis for gas explosion of coal mining and heading faces in underground coal mines. (August 2018) - Shi, Shulei; Jiang, Bingyou; Meng, Xiangrui; Yang, Li
During the past decade, gas explosions have been one of the most serious types of disasters in China, threatening the lives of miners and causing significant losses in terms of national property. This article, by constructing the fuzzy fault tree model of gas explosion on the coalface and heading face, deduces the minimum cut sets and minimum path of the fault tree, analyzes the importance of the fault tree structure, and obtains the ratio of gas explosion. The results show that the isolation of gas and heat sources is the most effective way to prevent gas explosion. In addition, a close detection of gas concentration and appropriate treatment can also avoid explosive accidents by reducing the ratio of explosion to below 0.059%, which is the critical value of explosion. The probability of gas explosion occurred in coal working face is about 0%–2.055%, and the most likely probability is 0.059%. However, the probability of gas explosion occurred in heading face is about 0%–8.543%, and the most probability likely to occur is 0.772% which is larger than that in coal working face. The fuzzy fault tree can not only be applied in the analysis of the coal mining gas explosion, but it also provides the theoretical basis for the precaution and prevention of coal mining accidents.